Groundwater dynamics of a lake-floodplain system: Role of groundwater flux in lake water storage subject to seasonal inundation - Song, Yanyan; Zhang, Qi; Melack, John M.; Li, Yunliang (The Science of the total environment, 2023)
Groundwater behaviors in lake-floodplain systems are dynamic and complex; in particular, the role of groundwater flux in regulating lake water storage subject to strong seasonal variation is not well understood. This study addresses the contribution of groundwater flux in a large floodplain system (Poyang Lake, China), with focus on quantifying the groundwater-lake interactions at multiple time scales in high rainfall (2010) and low rainfall (2011) years using a groundwater flow model (MODFLOW). Simulated results revealed that the unconfined aquifer received approximately 8 % of the annual rainfall as groundwater recharge. Fluctuations in shallow groundwater and lake water level reflected hydraulic synchronization and hysteresis. Additionally, the diurnal variability in the groundwater-lake exchange fluxes was subject to dynamic and bidirectional patterns, and a time lag between the water exchange and rainfall was also found. For 2010 and 2011, the monthly net flux of lake infiltration into groundwater was 1.5–10.0 mm and 0.1–6.0 mm and groundwater exfiltration into lake was 1.3–9.5 mm and 0.4–2.2 mm, respectively, demonstrating a significant variation of the exchange magnitude and direction. In particular, we found that groundwater exfiltration contributed up to 55 % of lake storage change in February of 2011. The outcomes from this study indicate that groundwater can be a major component of the Poyang Lake's water balance, which suggests an important role of groundwater in regulating the lake water storage and perhaps other flood pulse systems. [Display omitted] •Groundwater flow modeling of a lake-floodplain system quantified lake-aquifer interactions from daily to seasonal scales.•Groundwater-lake exchange fluxes responded to lake hydrological regimes and exhibited a large seasonal variation.•Floodplain groundwater contributed 55 % of the lake storage changes during a dry period.